2015
DOI: 10.1111/jam.12847
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of food-borne Bacillus volatile compounds and influence on fungal growth

Abstract: VOCs produced by Bacillus from cooked food can be considered as promising antifungal compounds useful in the control of fungal plant pathogens. This study investigates for the first time the correlation between mycelia inhibition of M. perniciosa and F. oxysporum f. sp. lactucae and the VOCs emitted by the Bacillus species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 32 publications
2
72
0
1
Order By: Relevance
“…Some of the detected compounds have been reported previously in microbial fermentation broths, including those from actinomycetes and Streptomyces sp. For instance, 2(5H)-furanone (1) (Braun et al, 1995), 2-ethyl hexan-1-ol (2) (Sunesson et al, 1997), 1-octanol (3) (Gu et al, 2007; Chaves-López et al, 2015), 1-undecanol (4) (Liu et al, 2015), 2-octanol (5) (Spreafico et al, 1997), phenol, 2,5- bis (1,1-dimethylethyl)- (6) (Zhang et al, 2013; Nandhini, 2015), ethyl 4-ethoxybenzoate (7) (Sharma et al, 2010), 1-tetradecanol (8) (Nhi-Cong et al, 2010), cyclo( L -Pro- D -Ala) (9) , cyclo(Gly-Pro) (10) (Ser et al, 2015b), cyclo(Leu-Pro) (11) , cyclo(Pro-Phe) (12) (Jog et al, 2014; Sharma et al, 2016) and phenol, 2,2′-methylene bis [6-(1,1-dimethylethyl)-4-methyl-] (13) (Tan et al, 2015b). …”
Section: Discussionmentioning
confidence: 99%
“…Some of the detected compounds have been reported previously in microbial fermentation broths, including those from actinomycetes and Streptomyces sp. For instance, 2(5H)-furanone (1) (Braun et al, 1995), 2-ethyl hexan-1-ol (2) (Sunesson et al, 1997), 1-octanol (3) (Gu et al, 2007; Chaves-López et al, 2015), 1-undecanol (4) (Liu et al, 2015), 2-octanol (5) (Spreafico et al, 1997), phenol, 2,5- bis (1,1-dimethylethyl)- (6) (Zhang et al, 2013; Nandhini, 2015), ethyl 4-ethoxybenzoate (7) (Sharma et al, 2010), 1-tetradecanol (8) (Nhi-Cong et al, 2010), cyclo( L -Pro- D -Ala) (9) , cyclo(Gly-Pro) (10) (Ser et al, 2015b), cyclo(Leu-Pro) (11) , cyclo(Pro-Phe) (12) (Jog et al, 2014; Sharma et al, 2016) and phenol, 2,2′-methylene bis [6-(1,1-dimethylethyl)-4-methyl-] (13) (Tan et al, 2015b). …”
Section: Discussionmentioning
confidence: 99%
“…Many signaling molecules used for communication between microorganisms are VOCs (Fernando et al, 2005; Chaves-Lopez et al, 2015; Giorgio et al, 2015). However, our results strongly suggest that overproduction of fengycins when B. amyloliquefaciens S499 is co-cultured with R. variabilis is not related to VOCs emitted by the fungus nor to the detection of molecular patterns harbored at the cell surface since the two partners were not in physical contact.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of fungal VOCs on CLPs production was evaluated on MRE medium using two-compartments Petri plates (Fernando et al, 2005; Chaves-Lopez et al, 2015). In the first compartment, the bacterium was inoculated by depositing a 10 μl drop of a cell suspension adjusted to an OD of 0.1, whereas in the second compartment, a mycelial disk of freshly pre-cultured R. variabilis was deposited.…”
Section: Methodsmentioning
confidence: 99%
“…Other research groups only occasionally identified single volatile compounds using authentic standards, while the remaining compounds were identified only by comparison with mass spectral databases (Tahir et al, 2017). In some cases it is not recognizable if volatiles were identified using authentic standards and/or libraries (Chaves-López et al, 2015). A clear assignment of an authentic standard confirmation was unfortunately missing.…”
Section: Identification Of Volatile Secondary Metabolitesmentioning
confidence: 99%